The structural arrangements in local government and their role in promoting community participation in basic service delivery: a case study of Emalahleni and Intsika Yethu local municipalities in the Chris Hani District Municipality area - Nqwemeshe, Nomvuyo (Rhodes University, Faculty of Humanities, Department of Sociology, 2012)
This study analyses the effectiveness of community participation in service delivery. The area of study, the Chris Ham District Municipality (CHDM), is a Water Services Authority, responsible for ensuring access to water services (water and sanitation) by all communities within its jurisdiction. There are eight local municipalities within the CHDM. The objective of this study is to determine whether systems are in place in local government to promote participation by communities in service delivery projects and whether these systems are being utilised efficiently by the role-players concerned. The role-players in this research are people who are involved in community development programmes of the municipality (municipal staff in the relevant departments of the municipalities under study, the social facilitators, civil society organisations, ward committees, ward councillors, traditional authorities as well as the representatives of communities (Project Steering Committees) who are beneficiaries of the projects under study). The projects that are under study were selected from a readily available list of CHDM capital projects that appear in the 2003/2004 financial year funding plan and are running. The findings of the study at both levels (local and district) show that the municipal environment is not conducive to promoting community participation. This is linked to factors such as the structural arrangements, whereby the offices relevant for promoting community participation are not fully occupied, which provided evidence that community participation is not prioritised. There is lack of coordination of programmes within the local government spheres as well within departments of the DM and strategies for community participation have been found to be non-effective. At project level lack of community participation is linked to the utilisation of ward committees as the only mechanism for community participation regardless of its un-equal and party biased representation. This study therefore concludes that although the systems to promote community participation are in place, they are not effective.
Keywords: Local government -- South Africa -- Eastern Cape; Municipal services -- South Africa -- Eastern Cape -- Citizen participation; Water utilities -- South Africa -- Eastern Cape -- Citizen participation; Water-supply -- South Africa -- Eastern Cape -- Citizen participation; Community development -- South Africa -- Eastern Cape; Economic development projects -- Evaluation -- South Africa -- Eastern Cape